EVALUASI KETERSEDIAAN RUANG TERBUKA HIJAU DI KOTA BEKASI (Universitas Esa Unggul, 2016)
This study discusses the availability of Green Open Space in the City of Bekasi, whether it is in accordance with ideal conditions or not. Tujan from this research is to identify the characteristics of green space contained in Bekasi City and to know what are the problems that hamper the fulfillment of ideal RTH in Bekasi City. Theories used in this research are evaluation theory, green city, and green space. While the main basis is Permen PU No.5 of 2008 on Guidelines for the Provision and Use of Green Ground in Urban Area. The research method used is descriptive quantitative with data collection techniques through literature study, observation and interviews with related agencies. The results showed that the availability of green open space in the city of Bekasi is still minimal and some types of green space are still under ideal conditions. In addition there are some problems that hamper the fulfillment of ideal RTH in Bekasi City so need to find a solution to overcome problems related to the existing green space in the city of Bekasi.Â Keywords: green open space, availability